Attention and mismatch negativity - Näätänen, R; Paavilainen, P; Tiitinen, H; Jiang, D; Alho, K (Psychophysiology, 1993)
The mismatch negativity (MMN) component of the auditory event-related potential (ERP) is elicited by infrequent, physically deviant stimuli in a sequence of frequent homogeneous stimuli (standards). It has been suggested that the MMN is generated by an automatic (attention-independent) neural mismatch process with a memory trace that encodes the physical features of the standard stimulus. The proposed MMN independence of attention was addressed in the present study. Standard stimuli and two types of deviant stimuli, differing from standards either in frequency or intensity, were dichotically presented in random order and at a rapid rate. The subject attended either to left- or right-ear stimuli, counting the number of a designated type of deviants in that ear. In the present conditions of very strongly focused attention, the MMN was elicited even by frequency change in the ignored input stream, and its amplitude was very similar to that of the MMN elicited by equivalent deviant stimuli (targets) in the attended input stream. In contrast, the MMN to intensity deviation was clearly attenuated in the absence of attention. This effect is, however, probably due to the attention effect on the MMN generator itself rather than the antecedent sensory-analysis and -storing functions.